Invasive infections due to Candida norvegensis and Candida inconspicua: report of 12 cases and review of the literature. (November 2013) - Guitard, Juliette; Angoulvant, Adéla; Letscher-Bru, Valérie; L'Ollivier, Coralie; Cornet, Muriel; Dalle, Frédéric; Grenouillet, Frédéric; Lacroix, Claire; Vekhoff, Anne; Maury, Eric; Caillot, Denis; Charles, Pierre Emmanuel; et al.
Abstract Candida inconspicua and Candida norvegensis are two closely related species rarely involved in invasive infections. The purpose of this study was to depict the epidemiologic and clinical characteristics of candidemia due to these emerging fluconazole less susceptible species. A retrospective analysis of the epidemiology of C. inconspicua and C. norvegensis during the period 2006–2010 was initiated in six French University hospitals. From this, demographics, clinical, diagnostic and therapeutic data of C. inconspicua or C. norvegensis candidemia were recorded and compared to the observations reported in the literature. C. inconspicua was more frequently isolated compared to C. norvegensis (ratio 2.6) but from the same preferential body sites: mainly digestive (56.4% and 48.37%, respectively, for C. inconspicua and C. norvegensis) and respiratory (26% and 28.2%, respectively). Thirteen cases of candidemia were recorded and five additional cases were found in the literature. Hematogical malignancy was the main underlying disease (n = 12). Associated factors were the presence of a vascular catheter (n = 18), broad-spectrum antibiotics (n = 15), and neutropenia (n = 14). In 13 cases (72%), prior colonization was noted before the candidemia diagnosis. Combining the results for the two species, Minimal Inhibitory Concentrations (MIC50) of amphotericin B, fluconazole, voriconazole and caspofungin were 0.125, 48, 0.25, and 0.19 mg/l, respectively. These two species must be added to the growing list of emerging Candida species poorly susceptible to fluconazole.